Perancangan Desain User Interface dan User Experience Web APE Cafe Menggunakan Figma dengan Pendekatan Design Thinking - Juan Philbert Artori Kris; Emy Lenora Tatuhey (CV Edujavare Publishing, 2025)
In the contemporary digital era, the design of user interfaces (UIs) and the subsequent experience of users (UEs) of systems and applications have become pivotal in enhancing the quality of interaction. It is evident that APE Cafe, a commercial entity operating within the culinary sector, necessitates a web design that is both intuitive and aesthetically pleasing in order to optimise the user experience. The objective of this study is to design the user interface and experience (UI/UX) for the APE Cafe website using the Figma software and a design thinking approach. The methodology employed comprises five stages: empathy, definition, ideation, prototyping and testing. During the empathy stage, researchers gathered information about user needs and expectations through interviews and surveys. In the subsequent phase, the identification and formulation of user problems was initiated. In the ideation stage, a variety of ideas for solutions were developed, followed by the creation of prototypes that allowed for design visualisation. In the final stage of the research process, the prototypes were subjected to a series of user tests with the objective of eliciting valuable feedback. The findings of the study demonstrate that the resulting design is aligned with user needs and enhances the quality of interaction. The utilisation of Figma resulted in enhanced efficiency and collaboration within the design process, enabling the team to expeditiously adapt to alterations and user feedback. It is anticipated that this research will positively contribute to the development of the APE Cafe website and enhance customer satisfaction through the provision of a superior user experience. Moreover, the findings of this study can function as a reference point for other businesses seeking to design effective and efficient user interfaces and user experiences.